Pengaruh Pandemi Covid-19 Terhadap Kunjungan Balita Di Posyandu Desa Wanggudu Alaa Kecamatan Asera Kabupaten Konawe Utara - Andi Tenri Angka; Yenni Yenni (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2021)
An integrated service post or often called posyandu is a health effort that is sourced from community resources, managed and organized from, for, by and with the community. The aim of the research is the influence of the Covid-19 pandemic on visits by toddlers to the posyandu in Alaa Wanggudu Village, Asera District, North Konawe Regency. The type of research used is a Cross Sectional Study. The samples in the research were all mothers with toddlers who came to the Alaa Wanggudu Village Posyandu, totaling 32 toddlers. The results of the research show that there is an influence of the COVID-19 pandemic on visits by toddlers at the posyandu in Alaa Wanggudu Village, Asera District, North Konawe Regency (p value = 0.039 < ? value = 0.05,) there is an influence of education on visits by toddlers to the posyandu in Alaa Wanggudu Village, District Asera, North Konawe Regency (p value = 0.031 < ? value = 0.05), there is an influence of anxiety level on toddler visits at the posyandu in Alaa Wanggudu Village, Asera District, North Konawe Regency (0.032 < ? value = 0.05), there is an influence of work on toddler visits at the posyandu in Alaa Wanggudu Village, Asera District, North Konawe Regency (p value = 0.027 < ? value = 0.05). The conclusion is that there is an influence of the COVID-19 pandemic, anxiety levels, work, education on visits by toddlers at the posyandu in Alaa Wanggudu Village, Asera District, North Konawe Regency. Suggestion: Mothers should continue to regularly take their children to the posyandu while still implementing health protocols.